2018
DOI: 10.1002/tea.21442
|View full text |Cite
|
Sign up to set email alerts
|

The technique of probing acceptance as a tool for teachers' professional development: A PCK study

Abstract: This article presents a study that examined an innovative short‐term program (two sessions of 3 hr each) for the professional development of teachers. The program design is based on the technique of probing acceptance, which is aimed at investigating student learning processes. It relies on students' evaluation, paraphrasing, and adaptation of information presented during a one‐on‐one interview with defined student‐centered interview phases. During the professional development program, teachers were introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
2
11
0
1
Order By: Relevance
“…These findings corroborate the fact that in all current working conceptualisations of Shulman's pedagogical content knowledge (PCK), teachers' knowledge of learners and their knowledge of instructional strategies are listed as distinctive dimensions (Park & Oliver, 2008;Wiener et al, 2018). Moreover, they highlight the notion that teachers are one of the essential factors in the science classroom and that their values and beliefs play a crucial role in the educational process (Anderson & Helms, 2001).…”
Section: Literature Reviewsupporting
confidence: 77%
“…These findings corroborate the fact that in all current working conceptualisations of Shulman's pedagogical content knowledge (PCK), teachers' knowledge of learners and their knowledge of instructional strategies are listed as distinctive dimensions (Park & Oliver, 2008;Wiener et al, 2018). Moreover, they highlight the notion that teachers are one of the essential factors in the science classroom and that their values and beliefs play a crucial role in the educational process (Anderson & Helms, 2001).…”
Section: Literature Reviewsupporting
confidence: 77%
“…Bekannt ist die Methode der Akzeptanzbefragung auch unter dem Begriff "Teaching Experiments", wie zum Beispiel bei [36,196,102]. In vielen Bereichen der didaktischen Forschung -nicht nur in der Physik -wurden Akzeptanzbefragungen zur Entwicklung von Unterrichtsansätzen eingesetzt [35,72,124,218,227], aber auch für andere Forschungsbereiche, zum Beispiel zur Erhebung von pädagogischem Wissen von Physiklehrkräften [219].…”
Section: Die Methode Der Akzeptanzbefragungunclassified
“…SMK is derived from various learning environments related to different ways of acquiring knowledge that changes over time. For example, in analyzing recent (i.e., January 2014 to September 2019) published research articles from key science education journals (i.e., Journal of Research in Science Teaching , Journal of Science Teacher Education , and Science Education ) we found that SMK has been studied from the perspective of in‐service teachers' professional development (Ogodo, 2019; Wiener et al, 2018), and elementary teachers' SMK has been studied more than that of secondary teachers (Donna & Hick, 2017; Nixon et al, 2019). Also, SMK is differentiated from content knowledge (CK) when referring to content knowledge in general outside the United States (Kulgemeyer & Riese, 2018; Großschedl, Harms, Kleickmann & Glowinski, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%